Prediction of ankle joint torques using artificial neural networks - Kopke, K.; Braman, J.; Bardel, C.; Khan, T.; Powell, J.; Udpa, L.; Haut, R. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Major ankle sprains in sports are thought to be due to high levels of ankle torsion. The purpose of this study was to develop a method for measuring in vivo ankle torques developed by athletes. Motion capture, force plate, and insole pressure measurements were used to develop generalized regression neural networks to predict maximum ankle torque and rate of ankle torque based on insole pressures. It was found that network prediction accuracy depended on the number of subjects used for training, as well as the method of pressure sensor grouping. Further work will be performed to determine optimal subject and pressure sensor groupings.